Socio Scientific Issue (SS1) Approach as a Momentum to Instill Cultural Literacy and Scientific Literacy Through Natural Science Learning - Wijaya, I Komang Wisnu Budi; Suryaningsih, Ni Made Ayu; Astiti, Kadek Ayu; Poerwati, Christiani Endah; Syahputra, Andika (FKIP Universitas Lampung, 2024)
Education is a process of cultural inheritance. Moreover, culture and science are also interconnected. However, the fact is that cultural and scientific literacy among students in Indonesia is still low. Therefore, improvements are needed in the learning process. One of the recommended learning approaches is learning with the SSI approach. This research aims to analyze how to instill cultural literacy and scientific literacy within the SSI approach. This research is classified as a literature review. Data is sourced from various literature such as journals, proceedings, theses, and other scientific sources. The collected data is then selected, reviewed, and analyzed, and subsequently synthesized in the discussion. The results of the discussion are summarized to form a conclusion. The research results state that the SSI approach can instill cultural literacy through the process of internalization, so that at every stage of the SSI approach, aspects of cultural literacy can be instilled, starting from the introduction of culture, cultural complexity, and cultural care. In addition, aspects of science literacy are also developed simultaneously, starting from the introduction of science in context, knowledge and processes of science, and the development of scientific attitudes. In applying the SSI approach to science education, teachers should be able to design lessons that integrate cultural and sociocultural aspects into science learning, as well as facilitate learning and assess the success of the education. Keywords: SSI approach, cultural literacy, scientific literacy.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp972-985